THE ASSOCIATION BETWEEN ALEXITHYMIA, SOCIAL SUPPORT AND QUALITY OF LIFE OF HYPERTENSIVE PATIENTS IN OWERRI MUNICIPALITY, IMO STATE - Cajethan Uchegbu, Ifechi; Ugokwe-Joseph, Rita; Valentine, Ucheagwu; Chinenyenwa Stephanie, Nnamdi; Onyinyechi Stellamaris, Onu (African Journal of Social and Behavioural Sciences, 2026)
This study investigated the association between Alexithymia, Social Support and Quality of Life of Hypertensive Patients in Owerri Municipality, Imo State. The study utilized a cross-sectional survey design. The participants responded to self-report measures, such as the Toronto Alexithymia Scale (TAS-20) developed by Bagby, Parker and Taylor (1994); The WHO quality of life (WHOQOL-BRIEF) questionnaire and the Multidimensional Perceived Social Support Scale (MPSSS) developed by Zimet, Dahlem, Zimet and Farley (1988). Two (2) hypotheses were postulated and tested. Three hundred and two (302) participants were drawn from different private hospitals in Imo State, using both purposive and convenience sampling techniques. The participants’ ages range between 35 and 74 years. The study used descriptive statistics and Hierarchical Multiple Regression to analyze the data. The results showed that social support (β = .24, t = 4.487, p < .01) significantly predicts the quality of life of hypertensive patients in Owerri Municipality. On the other hand, alexithymia (β = .40, t = -7.446, p < .01) negatively and significantly predicts the quality of life of hypertensive patients in Imo State. The study’s findings contribute significantly to the understanding of how social support and alexithymia intricately shape the quality of life of hypertensive patients in Imo State. The researcher recommends, thus, that clinical psychologists be posted to every healthcare facility for the well-being of hypertensive patients and others who may need their services.